2012
DOI: 10.2466/08.25.pms.115.6.865-880
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-Social Factors Determining Success in High-Performance Triathlon: Compared Perception in the Coach-Athlete Pair

Abstract: High-level sport can be analyzed using the complex system model, in which performance is constrained by many factors. Coaches' and athletes' perceptions of important positive and negative factors affecting performance were compared. Participants were 48 high-level international triathletes (n = 34) and their coaches (n = 14). They were personally interviewed via a questionnaire designed by four accredited experts, who selected groups of both positive and negative factors affecting performance. A list of factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…Research on psychological and social factors in triathlon is very scarce, and studies that relate these factors directly to performance are even rarer. The most influential positive factors for triathletes, both males and females, and coaches are dedication/commitment, perseverance, and work willingness [ 77 ]. These authors reported that the main negative factors are the injuries, together with a lack of personal confidence and competitive pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Research on psychological and social factors in triathlon is very scarce, and studies that relate these factors directly to performance are even rarer. The most influential positive factors for triathletes, both males and females, and coaches are dedication/commitment, perseverance, and work willingness [ 77 ]. These authors reported that the main negative factors are the injuries, together with a lack of personal confidence and competitive pressure.…”
Section: Resultsmentioning
confidence: 99%
“…We emphasize that the discrepancies mentioned above may depend on the approach adopted to carry out the analysis and the contexts examined. Specifically, (i) the amateur sport could differ substantially from the professional sport when the ability of athletes to respond to external stimuli is concerned [ 13 - 15 ]; (ii) fans' reactions could depend on the sport, season, and even the match or event in question [ 16 ]; (iii) the economic condition of the clubs could affect the performance of athletes [ 17 ]; (iv) supporters can often express disappointment during a match or sporting performance [ 2 ]; and (v) other psychological, social, and cultural variables could unpredictably alter sports performance [ 18 - 20 ]. Since the enormous damage caused by COVID-19 from a psychological point of view falls into the latter category of bias [ 21 , 22 ], it is necessary to interpret all the evidence found with caution.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that these tests are of very similar duration (62.0 ± 4.1 s for S100 and 62.5 ± 5.7 s for R400), the greater explanatory capacity of the swimming test may be related to the influence of speed over the first metres on triathlon performance (Vleck et al, 2008). Another possible explanation for the low predictive capacity of the talent identification tests in relation to performance factors in triathlon is that these tests are exclusively focused on the physiological component, contrary to the proposals of Abbot and Collins (2004), and do not take account of other factors with a higher influence on triathlon performance, such as anthropometric (Ackland et al, 1998;Landers et al, 2013), psycho-social (Ruiz-Tendero andMartin, 2012), mechanical (Bentley et al, 2002;Ofoghi et al, 2016) and tactical factors (Hausswirth et al, 2010;Ofoghi et al, 2016). Nor do they consider one of the distinctive features of triathlon compared to other long-distance cyclical sports: the influence of the preceding discipline on performance in the following segment (Bentley et al, 2007;Delextrat, 2005;Millet and Vleck, 2000).…”
Section: Discussionmentioning
confidence: 99%